2016
DOI: 10.1002/acr.22884
|View full text |Cite
|
Sign up to set email alerts
|

Association of Improvement in Pain With Therapeutic Response as Determined by Individual Improvement Criteria in Patients With Rheumatoid Arthritis

Abstract: ObjectiveTo use statistical methods to establish a threshold for individual response in patient‐reported outcomes (PROs) in patients with rheumatoid arthritis.MethodsWe used an analysis of variance model in patients on stable therapy (discovery cohort) to establish critical differences (dcrit) for the minimum change associated with a significant individual patient response (beyond normal variation) in the PRO measures of pain (0–10), fatigue (0–10), and function (Funktionsfragebogen Hannover questionnaire; 0–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…However, the strong association with pain is more surprising and supports the clinical relevance of a DAS28-d crit response as a surrogate for outcomes important to patients. The mean change in pain during tocilizumab and anti-TNF treatment exceeded the individual pain-d crit response value of 30 mm (corresponding to 3 points on a scale of 0 to 10 as calculated by Scharbatke et al [6]) in the DAS28-d crit responder group, but not in the group that did not achieve a DAS28-d crit response, suggesting that changes in pain associated with a DAS28-d crit response were clinically meaningful to patients. Patients with a DAS28-d crit response also showed strong improvements in patient-reported function as assessed by the HAQ-DI.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, the strong association with pain is more surprising and supports the clinical relevance of a DAS28-d crit response as a surrogate for outcomes important to patients. The mean change in pain during tocilizumab and anti-TNF treatment exceeded the individual pain-d crit response value of 30 mm (corresponding to 3 points on a scale of 0 to 10 as calculated by Scharbatke et al [6]) in the DAS28-d crit responder group, but not in the group that did not achieve a DAS28-d crit response, suggesting that changes in pain associated with a DAS28-d crit response were clinically meaningful to patients. Patients with a DAS28-d crit response also showed strong improvements in patient-reported function as assessed by the HAQ-DI.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have found that DAS28-d crit responses are associated with improvements in function as assessed by the Funktionsfragebogen Hannover patient questionnaire [3] and that patients with DAS28-d crit responses are more likely to achieve individual responses in PROs than patients who do not achieve a DAS28-d crit response [6]. In this study, we extend these observations by showing that DAS28-d crit responses were closely associated with In this study, the FACIT fatigue scale was reversed (0 = best; 52 = worst) so that lower scores were better, in keeping with other patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One contributing factor to this variation in treatment is when patients resist (refuse to adopt, avoid initiating/implementing, or discontinue) DMARD medication regimens recommended or prescribed by physicians . Patients’ resistance to DMARD treatment regimens can increase the risk of suboptimal treatment, prolong time spent with painful symptoms, and lead to progression of joint damage, diminishing patients’ current and future quality of life .
This qualitative study contributes to a better understanding of the role that feelings play in how patients with chronic conditions weigh the benefits and costs of medication treatments. For the rheumatoid arthritis (RA) patients in our study, feelings such as pain, loss, helplessness, shame, fear, protectiveness, anger, disappointment, and anxiety played an important role in motivating decisions to accept or resist disease‐modifying antirheumatic drug treatment regimens. Feelings in response to experiences of illness symptoms, medication side effects, identity as an RA patient, the act of taking medication, and the decision‐making process itself affected patients’ willingness to accept prescribed or recommended treatment.
…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have shown that employing a T2T strategy leads to lower disease activity and reduction of progressive joint damage, compared to routine care . Furthermore, studies have demonstrated that improvements in these disease‐specific outcomes are associated with reduced pain and improved physical function, health‐related quality of life, and work productivity , suggesting that minimizing the amount of time RA patients spend with MHDAS is beneficial. Even brief periods of MHDAS (<3 months) are associated with progression of joint damage and worsened short‐term and long‐term pain and functional deterioration .…”
Section: Introductionmentioning
confidence: 99%